Regeneration of ZVS converter with Resonant inductor - J.Sivavara Prasad; Ch.Sai Babu; Y.P. Obelesh (Institute of Advanced Engineering and Science, 2011)
This paper presents an analysis of the regeneration of zero-voltage-switching converter with resonant inductor, quasi-resonant converters, and full-bridge zero-voltage-switched PWM Converter. The design of a clamping circuit considering a saturable resonant inductor is presented and compared with the design of a clamping circuit with a linear resonant inductor. A diode model with reverse recovery is employed to simulate the effects.DOI: http://dx.doi.org/10.11591/ijpeds.v1i1.71